Factors Enhancing Treatment of Hepatitis C Virus–Infected Italian People Who Use Drugs: The CLEO-GRECAS Experience. (18th June 2021) - Rinaldi, Luca; Messina, Vincenzo; Di Marco, Vito; Iovinella, Vincenzo; Claar, Ernesto; Cariti, Giuseppe; Sacco, Rodolfo; De Luca, Massimo; Scifo, Gaetano; Gatti, Pietro; Barbarini, Giorgio; Pace Palitti, Valeria; et al.
Abstract : INTRODUCTION: We assessed the performance of direct-acting antivirals (DAAs) in hepatitis C virus (HCV)-infected people who use drugs (PWUDs) in terms of sustained virological response (SVR) and adherence rates in comparison to a location-matched cohort of non-PWUD HCV patients. METHODS: All consecutive HCV RNA-positive PWUDs were enrolled between 2015 and 2019. All subjects underwent DAA treatment according to international guidelines and then followed, at least, up to 12 weeks after the end of treatment (SVR12). The SVR and adherence to treatment was compared with that of non-PWUD HCV patients observed at hepatological units of the CLEO platform. Intention-to-treat analysis was performed. RESULTS: A total of 1, 786 PWUDs who were followed up were available for assessment. Most PWUDs (85.4%) were managed inside the specialized outpatient addiction clinics (SerDs). The overall SVR rate was 95.4%. The SerDs group achieved an SVR rate of 96.2% compared with 91.6% of the non-SerDs group ( P < 0.001). Comparison with the non-SerDs group and the control HCV group showed a significant difference in the dropout rate (0.6% in the SerDs group versus 2.8% in the non-SerDs group and 1.2% in the control group; P < 0.001). At multivariate analysis, factors independently associated with SVR were use of the most recent regimens (elbasvir/grazoprevir, glecaprevir/pibrentasvir, and sofosbuvir/velpatasvir; odds ratio: 3.126; P = 0.000) and belonging to the SerDs group (odds ratio: 2.356; P = 0.002). DISCUSSION: The performance of DAAs in PWUD is excellent, if 2 conditions are met: (i) that the latest generation drugs are used and (ii) that the patients are managed within the SerDs.